Pestplanten tromsøsvineblom Jacobaea alpina x subalpina i Norge - opphav og status - Alm, Torbjørn; Deschamps, Amandine Maria; Often, Anders (Norsk Botanisk Forening, 2016)
Jacobaea alpina (syn. Senecio alpinus, S. cordatus ) and J. subalpina (syn. Senecio subalpinus ) are native to the mountains of Central Europe. Both were cultivated as ornamentals in late 19th century Tromsø. From the early 1990’s onwards, numerous Jacobaea stands have been noticed outside gardens, in particular at Tromsø, but extending from Lenvik in central Troms northwards to Alta in Finnmark. Almost all specimens have been labeled as Senecio cordatus, i.e. Jacobaea alpina , but both the history of cultivation and the highly variable morphology of the plants suggest that this is unlikely . We have carried out a revision of the existing material, and re-visited a number of sites of supposed J. alpina and J. subalpina . With a single exception, it is not possible to assign the plants now found in North Norway to either species . Instead, they should probably be interpreted as a locally formed hybrid ( J. alpina × subalpina ) – which, unfortunately, turns out to be an aggressive alien. There are numerous stands in Tromsø, and at Slettaelva (Kvaløya island), a single stand comprises thousands or perhaps tens of thousands of plants, invading meadows, birch forest and in particular the damp areas along a brook.